ESTIMATING STORM DIRECT RUNOFF USING SYNTHETIC UNIT HYDROGRAPH METHODS BY (WMS) MODEL (SOLAG BASIN AS A CASE STUDY) - KHIDIR, KHALID M.; AL-SHA'AR, MOHANAD T. (Journal of Duhok University, 2017)
The Storm Runoff Volume and its Peak are important for designing and operating dams and different hydraulic structures. Watershed Modeling System (WMS) version (8.1) and The HEC-1 v (4.1) hydrological models were used in this study to estimate the Synthetic runoff hydrograph resulting from two storm events over Solag Basin which is located in Sinjar District north of Iraq, making use of available recorded storms rainfall and Synthetic unit hydrograph technique. Direct runoff hydrographs are determined using Natural Resources Conservation Service (NRCS), Snyder Synthetic Unit Hydrograph and Clark methods.Nash model was used to compare the efficiency of the Synthetic runoff Hydrograph using both Synthetic and recorded discharge data for Solag basin which were available for two storms within water years 1991-1992. Synthetic unit hydrographs are important in flood studies and water resources management.